2019
DOI: 10.1002/anie.201905129
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive Reversible Switching of Intersystem Crossing in Pure Organic Material for Smart Photodynamic Therapy

Abstract: Photosensitizers (PSs) with stimuli-responsive reversible switching of intersystem crossing (ISC) are highly promising for smart photodynamic therapy( PDT), but achieving this goal remains at remendous challenge.T his study introduces astrategy to obtain such reversible switching of ISC in an ew class of PSs,w hiche xhibit stimuli-initiated twisting of conjugated backbone.W ep resent am ultidisciplinary approachthat includes femtosecond transient absorption spectroscopyand quantum chemical calculations.The org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 40 publications
4
56
0
Order By: Relevance
“…Trying to overcome these drawbacks, some heavy‐atom‐free ROS‐PSs based on organic dyes have been reported recently . Although the origin of the photosensitizing capability in these dyes is still controversial, it has been suggested that structural distortion and charge‐transfer (CT) promotion upon the excitation could be involved in the enhanced probability of the ISC required to generate 1 O 2 (Figure ). In this context, promoting a charge‐transfer state (CTS) has been used recently to switch between fluorescence and ROS generation .…”
Section: Figurementioning
confidence: 99%
“…Trying to overcome these drawbacks, some heavy‐atom‐free ROS‐PSs based on organic dyes have been reported recently . Although the origin of the photosensitizing capability in these dyes is still controversial, it has been suggested that structural distortion and charge‐transfer (CT) promotion upon the excitation could be involved in the enhanced probability of the ISC required to generate 1 O 2 (Figure ). In this context, promoting a charge‐transfer state (CTS) has been used recently to switch between fluorescence and ROS generation .…”
Section: Figurementioning
confidence: 99%
“…Efficient long‐wavelength heavy atom‐free triplet photosensitizers are rare (Table S3). In this study, we got inspiration from distorted conjugated systems, which display elevated ISC efficiency . In particular, the removal of the mirror‐plane symmetry of a planar π‐system is considered to allow for a stronger spin orbit coupling (SOC) between π–π* states with different spin manifolds (the singlet state and triplet state), hence facilitating ISC .…”
Section: Introductionmentioning
confidence: 99%
“…photodynamic therapy (PDT) and photothermal therapy (PTT), has aroused wide attention on account of its unique advantages, such as deeper tissue penetration, negligible tissue injury, high efficiency, and specificity for cancer treatment. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Phototherapy also has its inevitable imperfection in spite of great progress achieved in the fields of PDT and PTT. For example, the hypoxia tumor microenvironment (TME) deteriorates the PDT efficiency and the heat shock response weakens the PTT effect.…”
mentioning
confidence: 99%